Diffusion Tensor Imaging Detects Clinically Important Axonal Damage after Mild Traumatic Brain Injury: A Pilot Study - Bazarian, Jeffrey J; Zhong, Jianhui; Blyth, Brian; Zhu, Tong; Kavcic, Voyko; Peterson, Derick (Journal of neurotrauma, 2007)
The goal of the current investigation was to detect clinically important axonal damage in cerebral white matter after mild traumatic brain injury (TBI) using diffusion tensor imaging (DTI). To this end, we evaluated a prospective, pilot study of six subjects with isolated mild TBI and six matched orthopedic controls. All subjects underwent DTI scanning, post-concussive symptom (PCS) assessment, and neurobehavioral testing within 72 h of injury. Fractional anisotropy (FA) and trace values in white matter voxels of whole brain and five preselected regions of interest (ROI) were compared in mild TBI and control subjects using a quantile approach. In addition, whole brain images were analyzed using voxel-based morphometry. All subjects underwent quality of life and repeat PCS assessment at 1 month. Whole brain images revealed significantly lower 1(st) percentile trace values (mean 0.465 vs. 0.488, p = 0.049) among mild TBI subjects. These trace values correlated with PCS scores at both 72 h (r = -0.57, p = 0.05) and 1 month (r = -0.61, p = 0.04). Analysis of ROIs showed mild TBI subjects to have significantly lower mean trace in the left anterior internal capsule (0.536 vs. 0.574, p = 0.007) and higher maximum ROI-specific median FA values (mean 0.801 vs. 0.756, p = 0.035) in the posterior corpus callosum. These FA values correlated with 72-h PCS score (r = -0.63, p = 0.03), and two neurobehavioral tests (visual motor speed [r = 0.63, p = 0.03] and impulse control [r = 0.59, p = 0.04]). Collectively, DTI detected significantly lower trace and elevated FA values in mild TBI subjects compared to controls. These abnormalities correlated to poor clinical outcome. We believe these findings represent axonal swelling, an early step in the process of axonal injury.